MARKETING MIX AND MARKETING ENVIRONMENT OF A SPORT ORGANIZATION - Nebojša Maksimović; Radenko Matić; Svetlana Mihić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
This paper analyses the basic elements of marketing (so called model 5P): product, price, distribution, promotion and staff as the main parts of marketing mix. It defines what can be an object of sale in terms of sport activity. Then, how the price is formed, what are the ways to sell the product, activity concerning product promotion as well as activity and service of the staff who are customer oriented.